Isolation and Identification of Lactic Acid Bacteria Using PCR Gene from Tempe Wrapped with Banana Leaves and Plastic - Fevria, Resti; Vauzia, Vauzia; Putri, Dwi Hilda; Achyar, Afifatul; Putri, Santi Diana; Edwin, Edwin (Indonesian Food Science and Technology Journal, 2024)
Tempe is a typical Indonesian food that comes from fermenting soybeans with the fungus Rhizopus sp. Tempe is known to have good nutritional value because of the content contained in soybeans themselves and other microorganisms that appear as a result of the tempe fermentation process. The fermentation process increases the activity of bacteria in tempe which are beneficial for digestion, one of which is lactic acid bacteria. This research aims to see the differences morphological forms  and genomic of lactic acid bacteria produced by tempe wrapped in banana leaves and tempe wrapped in plastic. The differences in fermentation that occurred in tempe wrapped in banana leaves and those wrapped in plastic resulted in differences in lactic acid bacteria type. Based on the isolation of bacteria on Mann de Rogosa Sharpe Agar medium, 15 isolates of lactic acid bacteria were produced, with general morphological forms of bacilli and coccus. Then, genomic identification was carried out using the PCR. The phylogenetic tree built based on the 16S rRNA gene sequence can show the relationship between LAB diversity at the species level, but cannot differentiate LAB from the strain level.